Assessment of mental wellbeing of undergraduate pharmacy students from 14 countries: The role of gender, lifestyle, health-related, and academic-related factors - Elnaem, Mohamed Hassan; Mubarak, Naeem; K. T., Mohammed Salim; Barakat, Muna; Abdelaziz, Doaa H.; Mansour, Noha O.; Thabit, Abrar K.; Ramatillah, Diana Laila; Al-Jumaili, Ali Azeez; Syed, Nabeel Kashan; Adam, Mohammed Fathelrahman; Hossain, Md. Sanower; et al. (Frontiers in Public Health, 2022)
Background: Quality education and wellbeing are part of sustainable development goals of the United Nations. Pharmacy students will assume a future role as frontline healthcare workers. Evaluating their current state of mental wellbeing and its associated factors is essential for better planning of students' support initiatives. The study objective was to assess mental wellbeing and its associated factors among undergraduate pharmacy students from 14 countries during the pandemic. Methods: A cross-sectional study was conducted among undergraduate pharmacy students in 14 countries belonging to three different WHO regions: Bahrain, Bangladesh, Egypt, India, Indonesia, Iraq, Jordan, Libya, Malaysia, Oman, Pakistan, Saudi Arabia, Sudan, and the United Arab Emirates. A 37-item questionnaire was developed, validated, and pilot-tested. The validated Warwick-Edinburgh Mental Wellbeing Scale (the 14-item WEMWBS) was adopted to assess mental wellbeing. Data collection was performed online between February 1st and April 15th, 2022. Inferential statistics were used to determine the factors associated with the students' mental wellbeing. Results: A total of 2665 responses were received, mainly from females (68.7%) with a higher presence of private universities (59.1%). About 34.9% had low mental wellbeing levels, while 57% and 8.1% had medium, and high levels, respectively. Higher mental wellbeing levels were reported among those who did not face challenges with online learning during the pandemic, those who chose the pharmacy program based on their interest and passion, and students with higher academic grades. Binary logistic regression showed that females (AOR=0.77, 95% CI: 0.64-0.92), those with chronic diseases (AOR=0.49, 95%CI: 0.36-0.68), and students who do not have normal BMI (AOR=0.86, 95%CI: 0.79-0.94) were less likely to have higher mental wellbeing scores. On the other hand, students who have been engaged in exercise (AOR=1.37, 95% CI: 1.19-1.57) and those from private universities (AOR=1.24, 95%CI: 1.05-1.46) were more likely to have higher mental wellbeing scores. Conclusion: More than a third of the participants were found to have low mental wellbeing levels. Students' mental wellbeing appears to be linked to various demographic, lifestyle, health-related, and academic-related factors. Careful consideration of these factors could help pharmacy schools plan programs, student services, and academic advising to improve students' mental wellbeing.